STUDI LITERATUR GADAI SYARIAH DAN RANTAI PASOK PEMBIAYAAN MIKRO - Pane, Sanusi Gazali; Soemitra, Andri (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 7 No 2 (2022): Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2022)
Pawn sharia (ar-rahn) is one element of microfinance for low-income groups. This study examines various types of articles related to sharia pawn microfinance in various national and international journals from 1990 to 2021. The main purpose of this paper is to examine the main trends and problems in sharia pawn microfinance. By using descriptive statistical analysis 35 articles or 70% in the form of journals, 5 articles are local publications, the remaining 30 articles are published in international journals. The conference consists of 6 articles or 12%, the proceedings are 3 articles or 6%, the master thesis and books are 2 pieces or 4% each, while the bulletins and dissertations are 1 or 2% each. The results of this study indicate that pawning as a microfinance supply net has not been widely discussed by researchers, but microfinance can be understood as a simple form of microfinance supply net.